The origin of diamond-bearing quartzite breccias from the Sopa Brumadinho Formation, Southern Espinhaço Range, Minas Gerais, Brazil (Revista Espinhaço, 2025)
The breccias of the Sopa-Brumadinho Formation, recognized as diamond-bearing since 1840, have had an igneous origin proposed since 1928. Their quartzite/metarenite clasts are millimetric to 50 cm, angular, pinkish to red in color, and similar to the substrate rocks. Their predominantly phyllitic matrix has a composition incompatible with that of igneous rocks, but REE data indicate a kimberlitic nature, with diamond xenocrysts, which can exceed 30 ct. The bodies (locally intrusive) have varying shapes—including a “champagne glass” shape—and reach up to 10 m thick and more than 50 m long. A proposed origin by cohesive debris flows from adjacent steep slopes appears unfeasible due to the consistent presence of diamonds in all deposits along a 50 km N–S extension. Since mudflows are not mineral concentrators and considering the absence of exotic material and the universal presence of diamonds, a proximal origin through the reworking of diamond-bearing tephra (tuff rings or pyroclastic surges) must be considered. Furthermore, the shape of the deposits and their contact relationships show that the breccias are confined within craters generated by phreatomagmatic volcanism, such as at Mina do Barro, where the breccias, circumscribed by quartzite walls, reach at least 60 m in depth. The physical characteristics of the gems reveal an absence of sedimentary reworking, and their mineral inclusions indicate a lithospheric origin for the diamonds. Regionally expressed lineaments appear to have acted as conduits for kimberlite magmas to reach the surface around ~1.7 Ga.
Keywords: Diamondiferous breccia; Sopa-Brumadinho Formation; phreatomagmatic volcanism; Southern Espinhaço range